ABRAHAM AND THE RHETORIC OF HOSPITALITY AND FOREIGNNESS IN HEBREWS AND 1 CLEMENT - Hartog, Paul (Science et Esprit, 2020)
Various studies have compared the Epistle to the Hebrews and 1 Clement in attempts to verify whether or not Clement borrowed from Hebrews. A minority of scholars have maintained that both Hebrews and 1 Clement employed shared, common tradition(s). The majority perspective, however, has argued for the likelihood of direct literary reliance. This essay turns in a new direction, by looking beyond the question of literary dependence (without denying its existence) to a comparison and contrast of a shared theme. The topic of hospitality remains an untapped vein of inquiry in the study of Hebrews and 1 Clement. By focusing upon the particular example of Abraham in Hebrews 11 and 1 Clement 10, one can demonstrate the distinctive yet overlapping outlooks of the two works. Hebrews, in view of its marginalized and oppressed audience, emphasizes the alien status of Abraham, who was looking for welcoming accommodation in a foreign country. 1 Clement, which addresses intergenerational conflict in the Corinthian congregation, highlights hospitality in welcoming and accommodating others, for the sake of communal harmony. The single figure of Abraham thus demonstrates that those who have received hospitality should in turn be hospitable to others.